Shifting family bilingualism: two South African case studies - Reynolds, Rose-Anne (School of Education, 2015)
This ethnographic, sociolinguistic study describes the home language practices of two Afrikaans/English bilingual families, living in two middle-class English-dominant neighbourhoods, with the youngest children attending an English-medium primary school. In this study, I investigate if these families maintain their existing Afrikaans-dominant bilingualism, or shift towards greater use of English. According to the sociolinguistic literature, there is an on-going relationship between the processes of language maintenance and shift. Factors that influence these processes include bilingualism, marriage patterns, socio-economic status, prestige of dominant languages, domains, educational environment, school peer group and attitudes as well as perceptions about languages and language use. The database consists of naturalistic observations, interviews and language diaries. Conversations between family members in their respective homes were audio-recorded (32 hours of observations in total) and open-ended interviews were conducted with family members about their language use and attitudes. The children completed language diaries where they self-reported their language use at home and at school. The findings are as follows: both families speak English, Afrikaans as well as varieties of English and Afrikaans characterised by code-switching, code-mixing and borrowings in the home. The Petersen family presents with intergenerational transmission and maintenance of Afrikaans from the mother and brothers to the younger daughters. ‘Teaching moments’ in this family, characterised by an active interrelationship between English and Afrikaans, result in the transmission and use of Afrikaans and English between the family members. As a result of the domestic Afrikaans maintenance, the two daughters continue to speak Afrikaans and express a positive attitude toward the language in general and their bilingual identity in particular.